2012
DOI: 10.1053/j.ajkd.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Progression Trajectory of GFR Among Patients With CKD

Abstract: Background The traditional paradigm of glomerular filtration rate (GFR) progression among chronic kidney disease (CKD) patients is a steady, nearly linear decline over time. We describe individual GFR progression trajectories over twelve years of follow-up among participants in the African American Study of Kidney Disease and Hypertension (AASK). Study Design Longitudinal, observational study Setting & Participants 846 AASK patients with at least 3 years of follow-up and 8 GFR estimates. Measurements Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
276
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(290 citation statements)
references
References 13 publications
10
276
1
3
Order By: Relevance
“…In addition, cross-sectional studies have shown that increased SBV is associated with increased renal resistive index, a marker of renal arteriosclerosis (6). Despite these potential mechanisms linking SBV with renal disease, SBV was not independently associated with renal events in our study, principally after controlling for proteinuria, which has been demonstrated in hypertensive individuals to be predictive of renal outcomes (15,(29)(30)(31)(32). In our analyses, the HRs for cardiovascular and renal events from highest compared with the lowest tertile of SBV decreased from 2.81 to 1.43 and 1.58 to 1.29, respectively, upon adjusting for log proteinuria.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, cross-sectional studies have shown that increased SBV is associated with increased renal resistive index, a marker of renal arteriosclerosis (6). Despite these potential mechanisms linking SBV with renal disease, SBV was not independently associated with renal events in our study, principally after controlling for proteinuria, which has been demonstrated in hypertensive individuals to be predictive of renal outcomes (15,(29)(30)(31)(32). In our analyses, the HRs for cardiovascular and renal events from highest compared with the lowest tertile of SBV decreased from 2.81 to 1.43 and 1.58 to 1.29, respectively, upon adjusting for log proteinuria.…”
Section: Discussioncontrasting
confidence: 63%
“…Of note, there was no relationship between total and LDL cholesterol levels and rate of change in GFR in the low proteinuria group (Table 5). This may relate to the overall slow decline in GFR in patients with lower levels of proteinuria with less power to detect an association; in addition, as shown in the African American Study of Kidney Disease and Hypertension study, nonlinear, abrupt declines in GFR are not uncommon in individual patients (29). This may contribute to why an association was seen between LDL and total cholesterol and clinical renal outcomes, but not with rate of decline in GFR.…”
Section: Discussionmentioning
confidence: 97%
“…Only a minority of units used predicted time to dialysis rather than eGFR to decide when to discuss the CKM option with a patient. Many patients with CKD have a nonlinear eGFR trajectory or a prolonged period of nonprogression in contrast to the traditional notion of steady GFR progression over time (24). This suggests that careful assessment of kidney disease progression is needed to decide when to discuss CKM with patients.…”
Section: Discussionmentioning
confidence: 99%